PERLINDUNGAN HUKUM TERHADAP PENGGUNA JASA KARTU FLEXI PADA PT. TELEKOMUNIKASI INDONESIA Tbk. CABANG JAMBI - Syarifa Mahila (Jurnal LEX SPECIALIS, 2010)
In this century wireless communication is become a common things not only for adult but also children to, but this condition is maybe solve one problem hard communication, but it also result another problem to like privacy, fund and due process of law to the server of this network, flexi as the one of many network cellural base on CDMA is not only give a good and simple communication but also make sure to give a protection of law to the user of this network, in condition to guarantee due process of law in the cellular reign.Key Note: Law protection to the user of Flexi